Perancangan Perumahan Dosen Berbasis Green Architecture di Kampus 4 Universitas Negeri Gorontalo: Integrasi Tata Ruang, Kenyamanan Termal, dan Keberlanjutan - Alvira Lerian Sugeha; Muh. Rizal Mahanggi; Satar Saman (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The design of Lecturer Housing for Campus 4 Gorontalo State University is a strategic necessity in line with the expansion of educational institutions and the increasing number of educators requiring adequate and proximate housing. The primary objective of this research is to produce a lecturer housing design that is not only adaptive and sustainable, but also harmonized with the Regional Spatial Plan (RTRW) of Bone Bolango Regency. The research methodology encompasses a comprehensive site analysis, examining aspects such as climate conditions, topography, vegetation patterns, infrastructure and utility networks, ambient noise levels, and site accessibility. Furthermore, a zoning and spatial relationship study was conducted to determine effective space allocation based on the principles of tropical architecture and green building practices. The findings of the study highlight that a north-south building orientation significantly reduces heat absorption, while the integration of cross-ventilation strategies enhances natural airflow and thermal comfort. Spatial zoning into public, semi-public, private, and service areas allows for organized layouts and promotes social interaction among residents. Sustainability is reinforced through the application of green architectural technologies, including the use of green concrete, lightweight steel frameworks, solar energy panels, as well as integrated waste-water management systems that separate black water and grey water. Landscaping elements, both softscape and hardscape, are utilized to enhance aesthetics while supporting ecological balance and rainwater absorption. This design proposal contributes to the broader discourse of sustainable tropical housing and may serve as a replicable model for future lecturer housing projects in similar regional contexts. It emphasizes the importance of environmentally responsive, cost-efficient, and socially supportive residential architecture.